2016
DOI: 10.1124/mol.116.104133
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Spinal Angiotensin II System in Streptozotocin-Induced Diabetic Neuropathic Pain in Mice

Abstract: Renin-angiotensin system (RAS) activity increases under hyperglycemic states, and is thought to be involved in diabetic complications. We previously demonstrated that angiotensin (Ang) II, a main bioactive component of the RAS, might act as a neurotransmitter and/or neuromodulator in the transmission of nociceptive information in the spinal cord. Here, we examined whether the spinal Ang II system is responsible for diabetic neuropathic pain induced by streptozotocin (STZ). Tactile allodynia was observed concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 50 publications
(69 reference statements)
3
25
0
1
Order By: Relevance
“…Recently, we have revealed that, in mice with STZ‐induced diabetes, the increase in spinal Ang II leads to an increase in phosphorylated p38 MAPK and neuropathic pain (Ogata et al, ). Moreover, the phosphorylation of other MAPKs such as ERK1/2 and JNK is also known to be involved in the STZ‐induced hyperalgesia (Middlemas et al, ; Tsuda et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have revealed that, in mice with STZ‐induced diabetes, the increase in spinal Ang II leads to an increase in phosphorylated p38 MAPK and neuropathic pain (Ogata et al, ). Moreover, the phosphorylation of other MAPKs such as ERK1/2 and JNK is also known to be involved in the STZ‐induced hyperalgesia (Middlemas et al, ; Tsuda et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…We have recently reported that the expression of spinal ACE is increased in STZ mice, which in turn leads to an increase in Ang II levels. Through AT1 receptor signalling, the elevated spinal Ang II levels produced tactile hypersensitivity and were accompanied by the phosphorylation of p38 MAPK (Ogata et al, ). We have also reported that the nociceptive behaviour induced in mice by an i.t.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations